A competitive radioimmunoassay using a monoclonal antibody to detect the factor X activator of Russell's viper venom. - Pukrittayakamee, S; Ratcliffe, P; Mcmichael, A; Warrell, D; Bunnag, D (1987)
A radioimmunoassay (RIA) has been developed for the detection of Russell's viper venom in body fluids. This is a competitive binding technique using a monoclonal antibody directed against the factor X activator of Russell's viper venom. The sensitivity of the test in urine was 4 ng/ml, in 0.1% bovine serum albumin-phosphate buffered saline it was 20 ng/ml and in serum it was 5 micrograms/ml. This was adequate to detect venom in the serum of four patients bitten by Russell's viper. Urine from an isolated kidney preparation perfused with Russell's viper venom contained coagulant activity and was positive using the competitive RIA. Testing of sera from other envenomated patients and pure venom from seven other species of snake indigenous to Thailand revealed RIA cross reactivity between cobra venom and Russell's viper venom. In practice, the absence of coagulant activity in cobra venom clearly distinguishes between the two. Although further development is required to elucidate the serum factors interfering with this assay, this is a promising technique, which is of potential value in the diagnosis and investigation of the pathophysiology of Russell's viper envenomation.